Aplicação de tensoativos não iônicos na recuperação de fluidos de perfuração poliméricos - Melo, Klismeryane Costa de (2013)
The drilling fluid used to assist in the drilling operation of oil wells, accumulates solids inherent in the formation as it is circulated in the well, interfering in the fluid performance during operation. It is discarded after use. The disposal of these fluids causes one of the most difficult environmental problems in the world. This study aims to promote liquid phase separation of drilling fluids, which have circulated in oil wells, and enable this recovered liquid to formulate a new fluid. For this, non-ionic surfactants were used in order to select the best outcome in phase separation. Five real water-based drilling fluids were utilized, which were collected directly from the fields of drilling oil wells, classified as polymeric fluids. The methodology used consisted in combining the fluid with surfactant and then subjecting it to a process of centrifugation or decantation. The decantating tests were scheduled through experimental planning 23 and 32, using as variables the percentage (%) of surfactant utilized and the stirring time in minutes. The surfactants used were ethoxylated nonylphenol and lauryl alcohol ethoxylated with different degrees of ethoxylation. Phase separation was monitored first by tests of stability, and subsequently by the height of the interface in beakers of 100 mL. The results showed that from the surfactants studied, the lauryl alcohol ethoxylated with 3 ethoxylation units has been the most effective in the phase separation process of the drilling fluids tested. The statistical tool used was of great industrial value regarding the programming phase separation in drilling fluids. In conclusion, the liquid phase separated using surfactant can be reused for a new formulation of drilling fluid with similar properties of a new fluid, assuring its efficiency. And in the resulting analysis it is also suggested that the adsorption is the mechanism that leads the phase separation, with surfactant adsorbing in the active solids